2019
DOI: 10.3390/hydrology6020054
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Pathways of Concentrated Submarine Groundwater Discharge in East Antarctica from Helicopter-Borne Electrical Resistivity Measurements

Abstract: The Southern Ocean receives limited liquid surface water input from the Antarctic continent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 64 publications
0
17
0
Order By: Relevance
“…Most of the active lakes are coastal (Fricker et al, 2007;Fricker & Scambos, 2009), have fill-drain cycles of months to years (Siegfried & Fricker, 2018), and discharge water under the grounded ice sheet into the sub-ice shelf ocean. There is also evidence for water flow from groundwater stored in East Antarctica (Foley et al, 2019) and from lakes in the continental interior (Wright & Siegert, 2012), implying wide hydrological dispersal of subglacial materials across Antarctica to the coastal margin.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the active lakes are coastal (Fricker et al, 2007;Fricker & Scambos, 2009), have fill-drain cycles of months to years (Siegfried & Fricker, 2018), and discharge water under the grounded ice sheet into the sub-ice shelf ocean. There is also evidence for water flow from groundwater stored in East Antarctica (Foley et al, 2019) and from lakes in the continental interior (Wright & Siegert, 2012), implying wide hydrological dispersal of subglacial materials across Antarctica to the coastal margin.…”
Section: Introductionmentioning
confidence: 99%
“…Shanhun et al 9 and Risk et al 54 suggested an abiotic origin of CO 2 based on the isotopic analyses, reporting very high positive φCO 2 values that cannot be explained by normal microbial activity. We suggest that the measured high anomaly values, originate from the subsurface brine system 31,49 , and are linked to permafrost cap discontinuities at the edges of the valley (fractures or buried local faults).…”
Section: Discussionmentioning
confidence: 87%
“…The MDVs are located within the Transantarctic Mountains and make up the largest ice-free region in Antarctica (Levy, 2013). Mean annual valley bottom temperatures in TV range from −14.7 to −23.0 • C (Obryk et al, 2020), and the region receives between 3-50 mm water equivalent of precipitation per year (Fountain et al, 2010). Lakes in the MDVs have 3-5 m thick perennial ice covers and vary in volume, chemistry, and biological activity (Lyons et al, 2000).…”
Section: Site Description and Field Campaignmentioning
confidence: 99%